Dacrystic Seizures: A Multicenter Video-EEG Study - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Children's Hospital, Boston; Boston University; Mayo Clinic, Jacksonville, FL; Northwestern University, Chicago; and the Cleveland Clinic in the USA; and centers in Germany and Spain studied the frequency of dacrystic seizures (DS) identified in video-EEG long-term monitoring units and the relationship of their clinical presentation to the underlying pathophysiology and etiology.